2001
DOI: 10.1073/pnas.101116298
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibitors I and II from potatoes block UVB-induced AP-1 activity by regulating the AP-1 protein compositional patterns in JB6 cells

Abstract: P lants typically respond to environmental stress such as insect herbivory, mechanical damage, and ultraviolet (UV) irradiation by inducing defense-related proteins (1, 2). Among these proteins, proteinase inhibitors I (Inh I) and II (Inh II) isolated from potato leaves are two well-characterized chymotrypsin inhibitors. Both proteins accumulate in potato and tomato leaves and are involved in signal transduction pathways in the plant's protective response against environmental herbivores and pathogens (3-5). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…4, lower panel). Hence, through PRB, and to a lesser extent PRA, progesterone increased the ratio of JunB, JunD and Fra-2 to c-Jun and Fra-1, an effect that is predicted to inhibit proliferation [16,27]. Thus, while overall AP-1 transcriptional activity was not changed by PRA Fig.…”
Section: Progesterone Differentially Regulates Ap-1 Dna Bindingmentioning
confidence: 71%
“…4, lower panel). Hence, through PRB, and to a lesser extent PRA, progesterone increased the ratio of JunB, JunD and Fra-2 to c-Jun and Fra-1, an effect that is predicted to inhibit proliferation [16,27]. Thus, while overall AP-1 transcriptional activity was not changed by PRA Fig.…”
Section: Progesterone Differentially Regulates Ap-1 Dna Bindingmentioning
confidence: 71%
“…Members of the AP‐1 protein complex, including JunD or Fra‐2, have been reported to inhibit cell transformation in vitro 35. Compared with JunD and Fra‐2, c‐Fos is more frequently considered as a pro‐oncogenic protein.…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 DNA binding was enhanced and the AP-1 complex contained primarily Fra-1 and JunD. Interestingly we have found that inhibition of UVBinduced AP-1 activation was also associated with an upregulation of JunD and Fra-2, and a suppression of c-Jun and c-Fos expression and composition in bound AP-1 in response to UVB stimulation (Liu et al, 2001). Balasubramanian et al (Balasubramanian et al, 2002) further showed that Ras, MEKK1, MEK3 and p38 kinase were involved in the cells' response to EGCG and additional studies suggested that p38 kinase was primarily responsible for the mediation of the response.…”
Section: Tea Inhibits Uv-induced Ap-1 Activationmentioning
confidence: 82%